Assalamualaikum may peace be upon you : observation on the islamisation of Malaysia - Zaid Ibrahim 1951- (ZI Publications Sdn Bhd, 2015)
The rise of political Islamisation in Malaysia in recent decades has raised many questions: what is the nature of this trend, what are its origins, who are its chief personalities, how has it grown, and, perhaps most pertinent today in the context of global events, what does it mean for Malaysia? Zaid Ibrahim explores these and other critical issues with the same passion, honesty, and even-handed rationality that distinguished his career as a Government minister and one of Malaysia's top lawyers. A leading social-political critic today, Zaid is known for his compelling discussions of some of Malaysia's most complex and divisive issues through an unshakeable commitment to the principles of justice, liberty, and democracy. Assalamualaikum should be read by all who are interested in the increasing religiosity of Malaysian politics and its implications on the constitutional fabric of a nation at the crossroads. Zaid Ibrahim was a practicing lawyer in Malaysia for over 33 years. He founded the law firm Zaid Ibrahim & Co., which has grown to be the largest law firm in Malaysia. He left the private sector to serve the government as de facto Law Minister in the Prime Minister's Department but resigned in protest against the use of preventive detention laws against civilians.